Comparison Analysis Of Rock Fragmentation After Blasting Between Imagej Analizer And Wipfrag Software - Abdul Jalil, Nurhanisah (Universiti Sains Malaysia, 2022)
This study was sought to study the comparison analysis of rock fragmentation after blasting between Image-J analizer and Wipfrag software. The field study was carried out at Imerys Malaysia Sdn. Bhd., Simpang Pulai, Perak, Malaysia. This study is organised into three phases: (1) site observation, (2) data analysis, and (3) experimental work. After blasting, images of the muck pile were taken using a handphone camera then were uploaded into ImageJ Analyzer and WipFrag software for fragmentation analysis of the particle size distribution graph (PSD) obtained from the software was correlated with the blast design. Fragmentation assessment data from several blast activities were then compared. UCS test results and structural data on field samples were also evaluated and correlated. From all four blasting sessions conducted, the cumulative pass percentage of the crusher ranged from 60 to 80 % for ImageJ while the range from 70 to 90 % for Wipfrag corresponded to the jaw crusher opening, 800 mm. Next, the lowest value point load test (PLT) was 2.03 MPa while the highest was 3.08 MPa which was significantly considered as medium strength. The analysis also found that there were three blasting activities with Powder Factor (PF) = 0.30 kg/m3 while session 4 which was PF = 0.54 kg/m3 was relatively high compared to the others. The boulder problem is also further influenced by the existing discontinuities at the blast site, depending on the direction, spacing, aperture and its condition, as well as other geological conditions including rock strength and layer thickness.